Primitive segmental infarction of the omentum - Belloso, Rogelio; Soto, José; Aliano, Artigas (Cirugía del Uruguay, 1976)
The authors record a case of infarction of the right border of the omentum without apparent torsion. They point out the fact that such is statiscally, the most common location.